Factors influencing local shoppers to shop at global online stores / Rabiatul Ain Md Said - Md Said, Rabiatul Ain (2015)
The development of dot com companies in 90s opened a new door of sales and revenue generation for the businesses worldwide. Online shopping has attracted a lot of attention in recent years due to its great potential for buyers and sellers. By enhancing understanding of online shopping, this study is to investigate “FACTORS THAT INFLUENCE LOCAL SHOPPERS TO SHOP AT GLOBAL ONLINE STORES” such as Lazada, Zalora, Groupon, and others online stores in Bangi area. In this study, four variables on factors that influence local shoppers were selected, namely perceived usefulness, shopping convenience, perceived pricing and online shopping intention. This research outlines a survey conducted with 200 respondents in Bangi area which is selected students and working professional who are engaged with online shopping due to ascertain the main factors that influence local shoppers to shop global online stores. Data collection procedure of this study by took the form of a self-administered online questionnaire by spreading through email and analyzed through multiple regression analysis by using SPSS. In this research, the outcome or result will be difference than previous researcher due to a researcher was not fielding same independent variables than previous research. Based on the findings, data that has been analyzed, it shows that positive significance of perceived usefulness, shopping convenience and perceived pricing with online shopping intentions which is more than 0.9. Furthermore, shopping convenience was the major dominant that has a strong significant with online shopping intention in correlation analysis.